2015
DOI: 10.7554/elife.05733
|View full text |Cite
|
Sign up to set email alerts
|

Viral-inducible Argonaute18 confers broad-spectrum virus resistance in rice by sequestering a host microRNA

Abstract: Viral pathogens are a major threat to rice production worldwide. Although RNA interference (RNAi) is known to mediate antiviral immunity in plant and animal models, the mechanism of antiviral RNAi in rice and other economically important crops is poorly understood. Here, we report that rice resistance to evolutionarily diverse viruses requires Argonaute18 (AGO18). Genetic studies reveal that the antiviral function of AGO18 depends on its activity to sequester microRNA168 (miR168) to alleviate repression of ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
196
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(200 citation statements)
references
References 60 publications
(107 reference statements)
3
196
1
Order By: Relevance
“…In vitro catalytic assays have shown that AGO2 and AGO5 possess a strong slicer activity against Tomato bushy stunt virus transcripts (Schuck et al, 2013). This is in contrast with AGO18, which does not appear to directly target viral RNA but rather functions by sequestering an endogenous microRNA targeting AGO1 (Wu et al, 2015). However, our results are in agreement with a previous study showing that the catalytic activity of AGO2 is required for defense against TuMV (Carbonell et al, 2012).…”
Section: Ago2 and Ago5 Associate With Pvx Rnascontrasting
confidence: 35%
See 1 more Smart Citation
“…In vitro catalytic assays have shown that AGO2 and AGO5 possess a strong slicer activity against Tomato bushy stunt virus transcripts (Schuck et al, 2013). This is in contrast with AGO18, which does not appear to directly target viral RNA but rather functions by sequestering an endogenous microRNA targeting AGO1 (Wu et al, 2015). However, our results are in agreement with a previous study showing that the catalytic activity of AGO2 is required for defense against TuMV (Carbonell et al, 2012).…”
Section: Ago2 and Ago5 Associate With Pvx Rnascontrasting
confidence: 35%
“…This induction is not dependant on the latter mutations as PlAMV, which infects Arabidopsis (Yamaji et al, 2012), induced AGO5 expression in wild-type Col-0 plants. Interestingly, it has recently been reported that AGO18, a member of a monocot-specific AGO protein clade, mediates virus resistance and is induced in virus-infected tissues (Wu et al, 2015). Whether systemic induction of AGO5 expression is induced by the presence of viral RNA itself, secondary vsiRNAs, or some other endogenous signal, and whether it shares similarities with AGO18 induction, remain to be elucidated.…”
Section: Ago2 and Ago5 Act Cooperatively To Counteract Pvx Infectionmentioning
confidence: 99%
“…More recent studies have revealed that some AGOs have additional functions. These include Arabidopsis AGO10 and rice AGO18 that act as decoys of specific miRNAs Wu et al, 2015) and AGO2 that mediates DSB repair (Wei et al, 2012;Ba and Qi, 2013). Below we discuss the actions and mechanisms of AGOs in association with different classes of sRNAs.…”
Section: Actions Of Plant Ago Complexesmentioning
confidence: 99%
“…Two plant AGO proteins, AGO10 in Arabidopsis and AGO18 in rice, have been demonstrated to compete with AGO1 for specific miRNAs and abrogate their activities through sequestration Wu et al, 2015). Arabidopsis AGO10 predominantly binds miR165/166, thereby preventing their loading into AGO1 and the subsequent repression of HD-ZIP III, targets of miR165/ 166 .…”
Section: Sequestrationmentioning
confidence: 99%
“…Most antiviral responses are investigated using dicotyledonous plants, but recently, AGO18 and miRNA528 were reported to be involved in antiviral responses in rice (Wu et al, 2015. In addition, two quantitative resistance genes against SCMV in maize have been identified (Leng et al, 2017;Liu et al, 2017).…”
Section: Zmvde Plays a Positive Role Against Scmv Infectionmentioning
confidence: 99%